NUMERICAL ANALYSES OF OPENFOAM'S OVERTOPPING DEVICE SOLUTION - Barbosa, D. V . E.; Souza, J. A.; Santos, E. D. dos; Isoldi, L. A.; Martins, J. C. (Revista de Engenharia Térmica, 2017)
Studies related to ocean energy are getting more important lately, once world claims for renewable energy usage. The Overtopping Device is a kind of Ocean Waves Energy Converter (OWEC), which main concept is storing water provided by incident waves above sea level to feed a set of low head turbines. In order to obtain the desired effect, this device contains a ramp which elevates the incident waves toward the reservoir. Present study aims to perform a numerical model of a 2D Overtopping Device by means of OpenFOAM simulations. OpenFOAM is a free open source code which has shown applicability in many areas of engineering. The adopted solver (InterFOAM) is Volume of Fluid based (VOF) according to Finite Volume Method (FVM), these methodologies has been largely used among researchers in propagating waves field. FLUENT (commercial code) is used to verify OpenFOAM's results. Once, the main point of this paper is to present OpenFOAM as a considerable tool for propagating waves studies, it firstly presents a numerical wave verification with analytical solutions (second order Stokes theory). The second section of results presents overtopping time series peaks in 100 s of simulation. Also, by mass flow rate integration, it presents total mas of water climbed to the reservoir. The integration of mass flow rate takes 94 s of simulation (not 100 s) because it is noticeable a pause between two peaks of overtopping at that time. Results show agreement between wave elevation and wave velocity profiles with straight convergence of periods between analytical and numerical waves. Most important differences are found near air/water interface, owed to faster air flow at that region. Generally OpenFOAM and FLUENT results are similar, with converged overtopping time series peaks and their magnitudes too. Similarly, the amount of water marked by both software are close with very similar trend lines.